Validation of Nine Different Prognostic Grading Indexes for Radiosurgery of Brain Metastases in Breast Cancer Patients and Development of an All-Encompassing Prognostic Tool - Weykamp, Fabian; El Shafie, Rami A.; König, Laila; Seidensaal, Katharina; Forster, Tobias; Arians, Nathalie; Regnery, Sebastian; Hoegen, Philipp; Deutsch, Thomas M.; Schneeweiss, Andreas; Debus, Jürgen; Hoerner-Rieber, Juliane (Frontiers in Oncology, 2020)
Purpose Several prognostic indexes for overall survival (OS) after radiotherapy of brain metastases in breast cancer patients exist, but are mainly validated for whole brain radiotherapy or not specifically for breast cancer patients. To date, no such index provides information beyond mere OS. Methods We retrospectively analyzed 95 breast cancer patients treated with stereotactic radiosurgery for 203 brain metastases. Kaplan-Meier method with log-rank test was used to assess OS, local control (LC), distant cranial control (DCC) and extracranial control (EC). Cox regression was applied to detect prognostic outcome factors. A point scoring system was designed to stratify patients based on outcome. Nine established prognostic indexes were analyzed using the concordance index (c-index). Results Two out of nine analyzed prognostic indexes for OS showed a significant c-index, the breast graded prognostic assessment (bGPA; 0.631; 95% CI, 0.514 to 0.748; p=0.037) and the modified bGPA (mod-bGPA; 0.662; 95% CI, 0.547 to 0.777; p=0.010). Significant results from multivariate analysis (Karnofsky Performance Score, Her2/neu receptor status, extracranial control) were used to generate a new point system: the breast cancer stereotactic radiotherapy score (bSRS), which discriminated three significantly different prognostic groups, for LC, DCC, EC and OS, respectively. However, the c-index was only significant for OS (0.689; 95% CI, 0.577 to 0.802; p=0.003). Conclusions The new bSRS score was superior to the bGPA and the mod-bGPA scores for prognosis of OS. The bSRS is easy to use and the first tool which might also provide outcome assessment beyond mere OS. Future studies need to validate these findings.